Preparation and characterization of Polyacrylonitrile/ Manganese Dioxides- based Carbon Nanofibers via electrospinning proce - Othman, F. E. C. (Institute of Physics Publishing, 2016)
This research reports the production of precursor polyacrylonitrile (PAN)/ manganese dioxide (MnO2) nanofibers (NFs) via electrospinning method followed by stabilization and carbonization processes. Nowadays, electrospinning has become a suitable method in manufacturing continuous NFs, thus it is employed to fabricate NFs in this study. The microstructural properties and adsorption competencies of the produced NFs were also studied. The NFs were prepared by electrospinning the polymer solution of Polyacrylonitrile (PAN) and Manganese Dioxide (MnO2) in, N, N-Dimethylformamide (DMF) solvent. The factors considered in this study were various polymer PAN/MnO2 concentrations which will significantly affect the specific surface area, fiber morphology and the diameter of the NFs prepared. Subsequently, heat treatment is applied by setting up the stabilization temperature at 275 oC and carbonization temperature at 800 oC with constant dwelling time (30 min). Nitrogen gas at constant rate 0.2 L/min was used for stabilization and carbonization with the stabilization rate (2 oC/min) and carbonization rate (5 oC/min). The CNFs produced were characterized using Scanning Electron Microscopy (SEM), Brunauer Emmett and Teller (BET) surface area and Fourier Transmission Infrared Spectroscopy (FTIR). It was found that the PAN/MnO2 CNFs were successfully produced with the carbonization temperature of 800 oC. The prepared PAN/MnO2 CNFs prepared showed an enhanced in specific surface area about two times compared to it precursor NFs.